Driver’s Shy Away Effect in Urban Extra-Long Underwater Tunnel - Chen, Ying; Du, Zhigang; Jiang, Zehao; Liu, Congjian; Chen, Xuefeng (Promet - Traffic&Transportation, 2023)
For urban extra-long underwater tunnels, the obstacle space formed by the tunnel walls on both sides has an impact on the driver’s driving. The aim of this study is to investigate the shy away characteristics of drivers in urban extra-long underwater tunnels. Using trajectory offset and speed data obtained from real vehicle tests, the driving behaviour at different lanes of an urban extra-long underwater tunnel was investigated, and a theory of shy away effects and indicators of sidewall shy away deviation for quantitative analysis were proposed. The results show that the left-hand lane has the largest offset and driving speed from the sidewall compared to the other two lanes. In the centre lane there is a large fluctuation in the amount of deflection per 50 seconds of driving, increasing the risk of two-lane collisions. When the lateral clearances are increased from 0.5 m to 2.19 m on the left and 1.29 m on the right, the safety needs of drivers can be better met. The results of this study have implications for improving traffic safety in urban extra-long underwater tunnels and for the improvement of tunnel traffic safety facilities.